Designing and assessing courses and curricula : a practical guide - Diamond, Robert M. (Jossey-Bass higher and adult education series, 2008)
Designing and Assessing Courses and Curricula reflects the most current knowledge and practice in course and curriculum design and connects this knowledge with the critical task of assessing learning outcomes at both course and curricular levels. This thoroughly revised and expanded third edition of the best-selling book positions course design as a tool for educational change and contains a wealth of new material including new chapters, case examples, and resources.